Utilization of Karanja (Pongamia pinnata) as a Major Raw Material for the Production of Biodiesel - Imran, Hossain Mohammad; Khan, Arafat H.; Islam, M. Shahinul; Niher, R.S.; Sujan, Asaduzzaman; Chowdhury, A.M. Sarwaruddin (Dhaka University Journal of Science, 2012)
An experimental process for the production of biodiesel using karanja (Pongamia pinnata) seeds as a raw material has been studied. This process involved transesterification of karanja oil with methanol in the presence of a catalyst (NaOH), to yield biodiesel as the main product and glycerin as by-product. In this research work, free fatty acid (FFA) of Karanja oil was determined and it was found less than 5%. As a result, one step transesterification was carried out. Oil to methanol molar ratio (6:1 to 12:1), variation (0.5% to 1.6% wt of oil) of Catalyst (NaOH) concentration was determined. Base-catalyzed transesterification converted karanja oil into biodiesel and glycerol using 1% NaOH as alkaline catalyst at 60-65°C. This study revealed the maximum yield of biodiesel up to 85% with methanol to oil ratio 1:9 and for 1.5 hr reaction at 65°C. Co-ignition of biodiesel with commercial diesel was also evaluated and it was found that diesel engine run smoothly in the ratio of commercial diesel to biodiesel was 7:3. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11506 Dhaka Univ. J. Sci. 60(2): 203-207, 2012 (July)